DYNAMICS OF SERUM IRON LEVELS IN POTENTIAL DONORS DURING PROTECTIVE INTENSIVE THERAPY - Lipnitski, A. L.; Marochkov, A. V.; Kupreyeva, I. A. (Zhurnal Grodnenskogo gosudarstvennogo medit͡s︡inskogo universiteta, 2025)
Background. At present, the dynamics of serum iron in organ and tissue donors with traumatic and non-traumatic brain injuries have not been reliably established. The aim of this study was to investigate the dynamics of serum iron levels in potential organ and tissue donors. Material and methods. The prospective study included 266 potential donors with brain death. The donors' serum iron levels were determined at three stages: stage 1 – after the 1st examination by the council to confirm brain death; stage 2 – 18-24 hours after the 1st examination by the council; stage 3 – after the 2nd examination and confirmation of brain death. Results. The iron level at stage 1 was 3.32 (2.26; 5.4) μmol / l (the iron level was within the reference values in 16 (6%) donors). At stage 2, the serum iron level was 3.23 (2.38; 5.32) μmol/l (p=0.96). At stage 3, the iron level statistically significantly increased to 3.59 (2.56; 6.02) μmol/l (vs stage 2, p=0.015). Donors with traumatic brain injury had lower iron levels at stage 1 compared to those with non-traumatic injuries: 2.67 (1.65; 4.24) μmol/l and 3.4 (2.49; 5.61) μmol/l, respectively, p=0.026. A statistically significant inverse correlation was found between the volume of intracranial hematoma and the serum iron level at stage 1 of the study: R=-0.29, p=0.05. Conclusions. In brain-dead potential donors, serum iron levels decrease significantly during protective intensive care.